2019
DOI: 10.1101/720151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Criticality as a determinant of integrated information Φ in human brain networks

Abstract: 21Integrated information theory (IIT) postulates that consciousness arises from the cause-effect 22 structure of a system but the optimal network conditions for this structure have not been 23 elucidated. In the study, we test the hypothesis that network criticality, a dynamically balanced 24 state between a large variation of functional network configurations and a large constraint of 25 structural network configurations, is a necessary condition for the emergence of a cause-effect 26 structure that results i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 69 publications
(66 reference statements)
1
27
0
1
Order By: Relevance
“…We assessed criticality using the pair correlation function (PCF), which is the variance of network synchronization, reflecting network susceptibility to internal and external perturbations (e.g., from stimuli; Yoon et al, 2015 ). PCF is maximal at a critical point and gradually decreases as a system moves toward a sub- or super-critical state (Kim and Lee, 2019 ). Recently, the reliability of PCF in evaluation of the level of consciousness was supported with a computational model and EEG during general anesthesia (Kim and Lee, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…We assessed criticality using the pair correlation function (PCF), which is the variance of network synchronization, reflecting network susceptibility to internal and external perturbations (e.g., from stimuli; Yoon et al, 2015 ). PCF is maximal at a critical point and gradually decreases as a system moves toward a sub- or super-critical state (Kim and Lee, 2019 ). Recently, the reliability of PCF in evaluation of the level of consciousness was supported with a computational model and EEG during general anesthesia (Kim and Lee, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, IIT has served as a theoretical framework for more practical measures such as the perturbational complexity index, which has been successful in differentiating levels of consciousness in the setting of physiological, pharmacological, and pathological perturbations (Casali et al, 2013). Furthermore, some surrogate measures of  have been successfully applied to altered levels of consciousness in humans (Kim et al, 2018) and also shown to relate to network factors such as topological modularity (Kim et al, 2018) or critical dynamics (Kim and Lee, 2019).…”
Section: Gnw and Other Theories Of Consciousnessmentioning
confidence: 99%
“…We constructed a binary adjacency matrix Aij using a threshold of 35%: if the wPLIij value of nodes i and j was within the top 35% of all wPLI values, Aij = 1; otherwise, Aij = 0. We chose a binarized approach to be coherent with the majority of studies assessing global network properties, which have also used a binarized approach to construct their graph 12,15,23,29,[68][69][70] . The 35% threshold was selected because it was previously shown, in the same dataset, to be the optimal threshold to avoid an iso- Figure 6.…”
Section: Methodsmentioning
confidence: 99%